The correlation between micronuclei count and smoking behavior: A hospital-based study - Lakshmi Balraj; UnniKrishnan K; Tejavathi Nagaraj (Universidad de Concepción., 2020)
Background: Micronucleus is a microscopically visible cyto-plasmic chromatin mass in the extranuclear vicinity, originating from aberrant mitosis, which consists of eccentric chromosomes that have failed to reach spindle poles during mitosis. The present study was designed to evaluate and compare cytogenetic changes in the buccal mucosa of smokers and non-smokers based on the occurrence of micronuclei. The study aimed to determine the correlation between the micronuclei count and the frequency and duration of smoking habit. Materials and Methods: Two groups (smokers and non-smokers) of 34 individuals each were examined. Cytological buccal smears were taken from participants using a moistened wooden spatula and stained with standard Papanicolaou stain. Presence of micronuclei was assessed at 40X magnification using a light microscope and a count per 500 cells was determined. The results of the study were analyzed statistically using Mann-Whitney U test, Spearman's rank correlation coefficient and Student t-test. Result: Smears from smokers showed a significant increase in the total number of micronuclei per 500 cell count compared to non-smokers. There was a strong positive correlation between the occurrence of micronuclei and the frequency and duration of smoking. A age-related increase in older age groups was also observed. Conclusion: The study reveals a strong positive correlation between the occurrence of micronuclei and the frequency and duration of smoking. This observation is vital in the utilization of the micronuclei detection in smears as a prognostic, educational and interventional tool in the management of patients with smoking habits.